Frontline Health Care Workers' (HCWs) perception of barriers to managing COVID-19 in Fiji - Deo, Anjana; Mohammadnezhad, Masoud (Frontiers in Public Health, 2022)
Background Health Care Workers (HCWs) are at higher risk of COVID-19 infection with their efforts while protecting the greater community and also exposed to hazards, such as psychological distress, fatigue, and stigma. This study aimed to explore the perception of frontline HCWs on barriers of managing COVID-19 in Fiji. Methods A qualitative study method was approached to conduct this study among the HCWs who worked on the frontline during the COVID-19 pandemic based at ten purposively selected health facilities in the Suva subdivision in the Central Division of Fiji. The Colonial War Memorial Hospital (CWMH), the Fiji Centre for Communicable Diseases (Fiji CDC), Twomey hospital laboratory, and CWMH laboratory did the main control and most of the operations of other divisions were monitored from these settings. A semi-structured open-ended questionnaire was used to collect data using in-depth interviews. The participants' responses were audio-recorded and were later transcribed and analyzed using thematic analysis. Results A total of twenty-nine HCWs took part in the in-depth interview and the responses were grouped into four themes, which include: workload, poor communication, lack of resources, and hindrance to education. It was also found through this study that some of the HCWs felt tired, frustrated, got rude to patients, and found it difficult to handle situations, which affected them mentally and physically stressed. Conclusion Managing the COVID-19 cases has been attributed to the presence of many barriers, such as workload, tiredness, frustration, and sometimes difficult-to-handle situations, and the HCWs were indeed affected mentally and physically. Regular training for HCWs and more awareness programs would help the general public to follow the preventive measures, which reduces the cases and would help the HCWs manage COVID-19 well.